In vitro effects of diosmin, naringenin, quercetin and indole-3-carbinol on fish hepatic CYP1A1 in the presence of clotrimazole and dexamethasone. (February 2018) - Sakalli, Sidika; Burkina, Viktoriia; Pilipenko, Nadezhda; Zlabek, Vladimir; Zamaratskaia, Galia
Abstract: Phytochemicals are widely present in fruits, vegetables and other plants and have great health benefits owing to their antioxidant properties. They are naturally found in the aquatic environment as well as discharged from sewage treatment plants after their large consumption. Little is known about their impact on fish; particularly in light of their interactions with pharmaceuticals. Therefore, this study was designed to determine the effects of diosmin, naringenin, quercetin and idole-3-carbinol on CYP1A-dependent 7-ethoxyresorufin-O-deethylase (EROD) activity on rainbow trout hepatic microsomes in the presence of two pharmaceuticals: clotrimazole and dexamethasone. The interactions between the phytochemicals and pharmaceuticals used in this study were determined using a combination index. Hepatic microsomes were exposed to two concentrations (1-or 50 μM) of phytochemicals and pharmaceuticals separately and in combinations. Singly, clotrimazole inhibited EROD activity 40% and 90% of control, while dexamethasone did not. Naringenin and diosmin inhibited EROD activity alone up to 90% and 55% respectively, but activities were further inhibited in the presence of either pharmaceutical. The preliminary study of combinations of clotrimazole with phytochemicals primarily showed synergistic effects. While EROD activity was not inhibited in the presence of quercetin or indole-3-carbinol, significant and synergistic inhibition was detected when either of these was combined with clotrimazole or dexamethasone. Highlights: Naringenin, diosmin and clotrimazole inhibited the EROD activity alone. Diosmin with high concentration of clotrimazole showed antagonistic behaviour. Quercetin, I3C and dexamethasone did not inhibit the EROD activity alone. Combination of dexamethasone and quercetin or I3C synergistically inhibited the EROD activity.